Pengaruh Digital Marketing Terhadap Keputusan Pembelian Secara Online di Shoope pada Mahasiswa Universitas Singaperbangsa Karawang - Laila Rahma Adila; Hartelina (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to examine the effect of digital marketing on online purchasing decisions of Universitas Singaperbangsa Karawang students on Shopee. The novelty lies in the use of digital marketing as a single variable through simple linear regression, focusing on students as digital natives. A quantitative approach was applied using questionnaire data from Shopee users among students, analyzed with simple linear regression. The results indicate that digital marketing has a positive and significant effect on purchasing decisions, contributing 60.4%. This highlights the essential role of digital marketing in raising interest and encouraging online transactions. The study is limited to students of Universitas Singaperbangsa Karawang and cannot be generalized widely. The findings provide practical insights for businesses to design more effective digital marketing strategies.